Intervention of One Rupee Rice in PDS: Utilisation and Impact in Andhra Pradesh and Odisha States in India - Mahendran, A (Asian Journal of Agriculture and Rural Development, 2014)
To find out the utilisation and impact of the scheme of pricing one kg rice at one rupee among the poor people and other beneficiaries at PDS outlets in Andhra Pradesh and Odisha states of India. For the purpose of this study, multi-stage random sampling method was used. Quantitative data was collected from the public using structured questionnaire. Data collection was done between 2nd December 2013 and 11th February 2014. The results show that more than 94.8% of poor families are utilising PDS grains in Odisha and 92.5% of BPL families are utilising PDS grains in Andhra Pradesh. In both the state’s 30% of the population is Above Poverty Line (APL) families, and they do not buy most of the commodities and more particularly in rice. As part of PDS reform, both these states have improved transparency with computerised ration shops and biometric ration cards and pin numbers. PDS outlets are more useful to poor people than for the Above Poverty Line families. This study suggests that allotments of rice for APL families must be cut to control corruption and leakages, this study also suggest that millets must be introduced in the PDS to increase nutrition security.